Amplification of fluorescence using collinear picosecond optical parametric amplification at degeneracy - 张静 张秋琳 江曼 张东香 冯宝华 张景园 (Chinese physics B, 2012)
We demonstrate the output characteristic of broadband parametric amplification of incoherent light pulses in a 355-nm pumped degenerate picosecond optical parametric amplification with either saturated or unsaturated amplification. The optical parametric amplifier is seeded by the fluorescence generated in a solution of pyridine-1 dye in ethanol. With the saturated amplification, we can obtain high energy incoherent light pulses, whose full width at half maximum bandwidth varies from 16 nm to 53 nm for the different phase matching angles near degeneracy. Moreover, the unsaturated bandwidth of the amplified pulses fits well to the calculated result at degeneracy. Selecting s-polarized fluorescence with a Glan-Taylor prism, the maximum bandwidth of the amplified fluorescence is found to be 59 nm for a purely s-polarized seed. The maximum output energy is 0.67 mJ for the optical parametric amplifier. By using an optical filter and compressor, the generated high energy incoherent light has great potential as the incoherent pump, signal or idler wave of a parametric down-conversion process, so that a wave with a high degree of coherence can be generated from an incoherent pump light.